Microstructure evolution during novel rheorolling process for producing A356 alloy strip. (May 2013) - Guan, R G; Zhao, Z Y; Wang, X; Lee, C S; Liu, C M
Abstract : Microstructure evolution during a novel rheorolling process for producing A356 alloy strip was investigated. Under the high cooling rate caused by the sloping plate and stirring action caused by the vibration and metal flow, high nucleation rate and dendrite breakage happened during the process, which causes the formation of fine spherical or rosette primary grains. The grain size of the primary α -Al phase decreased with the decrease in casting temperature in the cooling slope, but the volume fraction of the primary α -Al phase increased. The change of the primary grain shape is not obvious in the roll gap during the rolling process, and most of the primary grains nearly kept round or rosette shapes. When the casting temperature is 660°C, the strip with a cross-section of 4×160 mm was produced, and homogeneous microstructure was obtained.